Management of Pre-emergence and Post-emergence Damping Off Disease of Chilli Through Seed Treatment - Azad, C. S.; Singh, R. P.; Kumar, A.; Rautela, P.; Gupta, S. (International Journal of Bio-resource and Stress Management, 2023)
Pre-emergence and post-emergence damping off is one of the serious concerns for vegetable nurseries. Pathogens like Alternaria spp. and Colletotrichum spp. are known to be associated with the chilli seeds and cause considerable loss in seed germination and results in seedling mortality. Damping off is mainly seed borne and soil borne, the initial infections are needed to be controlled with suitable fungicides and bioagents as seed treatment. The results indicate that among different fungicides seed treatments with thiram 75 WS+carbendazim 50 WP (2:1) @ 3 g kg-1 seed was found superior with significantly higher seed germination as compared to other treatments and control. Maximum seed germination (55.19%) and minimum seedling mortality (24.45%) along with maximum seedling vigour index (1409.37) was recorded in seed treated with thiram 75 WS+carbendazim 50 WP (2:1) @ 3 gm kg-1 seed followed by thiram with seed germination of 50.71% and seedling mortality of 26.91%. Carbendazim 50 WP was found at par with thiram 75 WS. Among bioagents Trichoderma harzianum strain PBAT 21+Pseudomonas fluoresens strain PBAP 27 @ 10 g kg-1 seed proved to be the better in all respect over others. Among bioagents maximum seed germination (43.88%) and minimum seedling mortality (35.82%) along with maximum seedling vigour index (759.00) was recorded in seed treated with Trichoderma harzianum strain PBAT 21+Pseudomonas fluoresens strain PBAP 27 @ 10 g kg-1 seed followed by Trichoderma harzianum PBAT-21 @ 10 g kg-1 seed with seed germination of 41.52%, seedling mortality of 39.82%.